ACTIVITY OF MAKASAR FRUIT (Brucea Javanica L. Merr) ON RADICAL ANION SUPEROXIDE IN VIVO - Ari Widiyantoro; Elvi R.P. Wardoyo; Endah Sayekti (Jurnal Penelitian Saintek, 2010)
Activity  of scavengering  radical  anion superoxide  by extract of Makasar fruit  (Brucea javanica   L. Merr)  have  been  research  with  methods  of  inhibition  reduction  nitroblue tetrazolium,  by in vivo on rat  Wistar induction with aflatoxin. Results showed  there are inhihition  reduction  of  nitroblue  tetrazolium  by  methanol  extract,  methanol fraction, ethylacetate fraction,  methylen chloride fraction  and n-hexane fraction. Phytochemical test showed alkaloid, terpenoid, quinone, polyphenol and steroid.